2007
DOI: 10.1002/ajim.20490
|View full text |Cite
|
Sign up to set email alerts
|

An old threat in a new setting: High prevalence of silicosis among jewelry workers

Abstract: In this study we demonstrate that use of chalk molds in casting in jewelry causes silicosis. The composition of the dust could be responsible of the high prevalence observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…12,13,18,21 It should also be noted that carpenters and joiners had significant mean RCS exposure levels (AM50.047, 93% of exposure measurements above the ACGIH limit value), comparable with those of miners and quarry workers (AM50.048, 97% of exposure measurements above the ACGIH limit value), likely reflecting an inadequate implementation of preventive measures to control workplace silica dust air concentrations in the Italian construction industry, similar to other economically developed countries. [19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values. This may be due to the significant decrease of airborne RCS concentrations reported in the ceramic industry over time, 14,22 and to the high variation in whether workers use dry or automated/remotely controlled working methods.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…12,13,18,21 It should also be noted that carpenters and joiners had significant mean RCS exposure levels (AM50.047, 93% of exposure measurements above the ACGIH limit value), comparable with those of miners and quarry workers (AM50.048, 97% of exposure measurements above the ACGIH limit value), likely reflecting an inadequate implementation of preventive measures to control workplace silica dust air concentrations in the Italian construction industry, similar to other economically developed countries. [19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values. This may be due to the significant decrease of airborne RCS concentrations reported in the ceramic industry over time, 14,22 and to the high variation in whether workers use dry or automated/remotely controlled working methods.…”
Section: Discussionsupporting
confidence: 59%
“…These workers, although they represent a small proportion of Italian workers, should be targeted for prevention measures, including dust abatement programs and risk awareness education initiatives. 26 Overall, 50% of exposed workers had an exposure value exceeding the limit (TLV) proposed by ACGIH (and 44% had exposure values exceeding SCOEL recommendations). This indicates that there is a need for addition and more intense dust control and information interventions.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of a relationship between spirometry and radiographic changes was found in studies in which nonexposed controls were used, but not in the case of silica-exposed controls. 32,33 In addition, a different latency period after silica exposure for the development of spirometry and radiographic changes would cause the results from the studies of current and retired workers to differ.…”
Section: Discussionmentioning
confidence: 94%
“…[15] But, apart from the study of Murgia et al .,[6] no study was reported, which could show the occupation-induced physiological changes, especially respiratory changes amongst the goldsmiths. Some reports showed that the mortality rates of the workers of jewelery industries increased due to cancer.…”
Section: Introductionmentioning
confidence: 99%